Molecular Pathology of Nervous System Tumors: Biological Stratification and Targeted Therapies - Karajannis, Matthias A. (Molecular Pathology Library, 2015)
This book serves as a comprehensive guide to the rapidly evolving field of molecular neuropathology of nervous system tumors, as well as the underlying biology and emerging molecular targeted therapies. Special emphasis is given to already established and emerging molecular diagnostic tests in neuropathology, as well as molecular targeted therapies. The book is organized by clinico-pathologic disease entities, and each chapter is written by a team of experts in their field. Molecular Pathology of Nervous System Tumors is of great value and utility for physicians and scientists involved with or interested in the up-to-date diagnosis and treatment of patients with brain tumors